The Role of Servant Leadership, Organizational Support and Knowledge Sharing in Improving Tax Employee Performance: Peran Servant Leadership, Dukungan Organisasi dan Knowladge Sharing dalam Meningkatkan Kinerja Pegawai Pajak - Jeffri Maulana; Rifdah Abadiyah (Academia Open, 2021)
This study aims to determine the effect of Servant Leadership and Organizational Support on Employee Performance with Knowledge Sharing as an intervening variable at DGT Tax Services Sidoarjo Barat. This research is a type of quantitative research with hypothesis testing. The sample used in this study were all employees of the West Sidoarjo Tax Service DJP as many as 148 employees. The sampling technique used the probability sampling method. The analytical tool used in this research is a path analysis technique with the help of software for the operating system called Smart-PLS (Partial Least Square) Version 3.2.9. The data used in this study are questionnaire data and data sourced from the DGT of Tax Services in West Sidoarjo. Data collection techniques using questionnaires, interviews, observations, and documentation. The results of this study prove that Hypothesis 1: Servant Leadership variable has a significant effect on Knowledge Sharing, while Organizational Support has a significant effect on Knowledge Sharing, and Knowledge Sharing has a significant effect on Employee Performance. Hypothesis 2: Servant Leadership variable has no significant effect on employee performance, while organizational support has a significant effect on employee performance. Hypothesis 3: Organizational Support Variable has no significant effect on Employee Performance through Knowledge Sharing as an intervening variable, while Servant Leadership has a significant effect on Employee Performance through Knowledge Sharing as an intervening variable